Corporate Social Responsibility: Strategic Perspective on Why It Is a Necessity and How to Gain Competitiveness from Being Socially Responsible - Lee, Raymond Long Heng (2007)
Over the past decade, Corporate Social Responsibility (‘CSR’) has emerged as one of the most important strategy in this present time. It had evolved from a concept to become one of the most influential concepts that are being deployed by companies worldwide. As such, many academicians have attempted to look into this concept from various viewpoints. Despite the inability to come out with a clear definition and also the lack of empirical study on this concept but nevertheless, Corporate Social Responsibility have continue to establish itself as the most influential corporate strategy. For the purposes of this dissertation, this paper will firstly attempt to evaluate the importance of CSR and how does it evolve to become global strategy. The main focus of this study would be to determine the reason WHY and HOW do companies perform their social responsibility. Therefore, 4 companies from 2 industries (namely, the F&B and Automotive industry) will be chosen as case study in this dissertation. Lastly, this dissertation will look whether there are any similar (isomorphism) patterns of CSR that existed between the F&B and Automotive industry. The results signified that there is there conclusive evidence that WHY there is specific purpose of companies adopting CSR as their business strategy and HOW they gain competitive advantage from such activities. Besides that, it also appears to be similar patterns of CSR strategies that being deployed between the F&B and Automotive industry.